Cultivating Self-Regulated Learning (SRL) in A-Level Students Through Hyper Learning Environments (HLE) A Conceptual Synthesis - Adeeba Khurshid (Research Journal of Psychology, 2025)
This study explores how self-regulated learning (SRL) can be cultivated among A-Level students within Hyper Learning Environments (HLEs)—instructional settings that emphasize innovative pedagogical design, student agency, and active participation. Drawing upon social cognitive theory (Zeidner & Stoeger, 2019) and supported by empirical literature (Guven & Babayigit, 2020), the study examines four key propositions: (1) High-achieving students exhibit advanced SRL competencies, particularly in planning and time management; (2) Students with underdeveloped SRL skills in HLEs demonstrate weaker conceptual mastery; (3) The quality of SRL processes is directly associated with academic performance; and (4) Teachers’ awareness of their own professional learning practices enhances their capacity to foster SRL in students. Through systematic content analysis of peer-reviewed research, the findings affirm that HLEs incorporating problem-based learning (PBL), teacher modeling, and structured goal-setting mechanisms effectively nurture SRL behaviors. The discussion emphasizes the importance of cultivating self-efficacy, goal intention, and implementation planning (e.g., “if–then” strategies) as integral components of SRL. It also highlights the role of the social environment—including peer and teacher support—in shaping students’ self-beliefs and regulatory capacities. Limitations include reliance on secondary data and the need for localized empirical validation. This research contributes to ongoing efforts to humanize instructional design and embed SRL-focused interventions within Pakistani A-Level institutions.